Rare Occurrence of RHD Null Alleles With Del Expression Among Serologically D-Negative Blood Donors - Lilić, Marko; Guzijan, Gordana; Jovanović Srzentić, Snežana (Scripta Medica, 2024)
Background/Aim: An investigation into the diversity of serologically D-negative blood donors in the Republic of Srpska entity of Bosnia and Herzegovina forms the basis of this research. The primary purpose of the study was the examination of RHD variants over a period of five years. Methods: A comprehensive depiction of the RHD distribution in D-negative blood donors is achieved through a combination of serological observations and DNA testing (PCR-SSP with fluorometric signal detection), involving 74,149 blood donors. The adsorption/elution method was used to confirm the Del phenotype. Results: A small fraction (0.31 %) of the serologically D-negative blood donors was found to contain eight different RHD alleles. The Del phenotype of the RHD*01N.03 and RHD*01EL.44 alleles was highlighted, challenging the common perception that these alleles are associated exclusively with a D-negative expression. Conclusion: The importance of molecular methods in analysing and understanding Del variants, which typically elude conventional serological assays, is underscored by the findings. A group of donors seemingly having the RHD*01 allele but who lacked D antigen expression was encountered, hinting at the potential presence of still unidentified, possibly geographically restricted, RHD variants or alterations in other genes responsible for the expression of Rh proteins in the erythrocyte membrane.